Penerapan Model Direct Instruction Berbantuan Media Power Point untuk Meningkatkan Hasil Belajar Siswa Kelas I SD Negeri 4 Sebatu Tahun Ajaran 2020/2021 - Ni Made Sulastriningsih; Sulfan Efendi (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
This research was carried out at SD Negeri 4 Sebatu in Class I, where the ability and learning outcomes of students to study Theme 3 My Activities were still low. The purpose of writing this classroom action research is to find out whether student learning outcomes can be improved by applying the steps of the Direct Instruction learning model. The data collection method is a learning outcome test. The results obtained from this study are student learning outcomes can be improved by applying the steps of the Direct Instruction learning model. 65.36 with a percentage of classical completeness 46.42% and an increase in the second cycle the average value becomes 68.92 with a percentage of classical completeness 85.71%. The conclusion obtained from this study is that student learning outcomes can be improved by applying the steps of the Direct Instruction Learning Model.